Failure to convulse with electroconvulsive therapy. A case report - Sharpe, M; Andrew, B (1988)
A case is reported of a severely depressed patient in whom treatment with electroconvulsive therapy was abandoned because of repeated failure to induce a convulsion. Reasons for the failure to convulse and alternative treatment approaches are discussed.